Are Chinese paying too much or too little for school quality? The rent yield gap approach for estimating the capitalization of school quality in Shanghai - Muyang Zhang; Jie Chen (Asian Development Bank Institute (ADBI), 2017)
This paper explores how the unequal right of enrollment for public schools between households with different tenure statuses in urban People's Republic of China (PRC) affects rental yields. In the PRC, the rental yield is as low as 2% in major cities, mostly due to the lack of property tax and the lasting boom in real estate prices. Using a hedonic pricing model, we find that the rental yield in neighborhoods associated with high-quality schools is 0.1-0.4 percentage points lower than those associated with ordinary schools, but the estimated opportunity cost of accessing high-quality schools is around CNY90,000-CNY100,000, which is affordable for many families. However, "tenant discrimination" for the right of enrollment of public schools, accompanied with tight credit constraints, creates high entry costs that prevent children from middle-income families from attending high-quality schools, thus allowing families with high initial wealth to access better education at a lower cost. This paper provides a new perspective on the results of education equalization programs in terms of educational and residential segregation and intergenerational mobility. It also adds important new insights into the studies on household behavior in the PRC's housing market during the country's rapid urbanization process. The policy implications of our study are discussed in the concluding section.
Keywords: H44; I24; R38; 330; school quality; tenant discrimination; rental yield; credit constraint; People's Republic of China